EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA: SUATU KAJIAN META-ANALISIS - Ariansyah; Yatin Mulyono (Jurnal Metabio, 2025)
This study aims to examine the effectiveness of the inquiry-based learning model in enhancing students' critical thinking skills through a meta-analytic approach. The research background is based on the low level of critical thinking skills among Indonesian students, primarily due to the dominance of conventional teaching methods. The inquiry model is considered a solution as it positions students as active participants in the learning process. This study collected data from seven nationally indexed SINTA articles that met the inclusion criteria, with quantitative data including means, standard deviations, and sample sizes. The meta-analysis results showed an average effect size (Cohen’s d) of 0.82, which is categorized as moderate to large, indicating that the inquiry model is generally effective in improving students' critical thinking skills. However, one study reported a negative effect size, suggesting that the effectiveness of the inquiry model is highly influenced by teacher readiness, student preparedness, and resource support. The implications of this research highlight the importance of teacher training, curriculum development, and the provision of supporting facilities for optimal implementation of the inquiry model. The study recommends expanding research to other educational levels and disciplines and employing more rigorous research designs to strengthen the generalizability of the findings.